The Educational & Political Philosophy of Maulana Abul A‘la Moudodi: A Historical Review - Ismail , Muhammad; Ahmad Khan , Dr. Mumtaz; Hayat , Dr. Khizar (Al-Amīr Research Journal for Islamic Studies, 2024)
The present paper narrates the educational and political philosophy of an Islamic state by analyzing the religious foundations of Maulana Abul Ala Maudodi’s theory of politics. His theory of politics rotates around the content of cognition that religion and politics entities are unable to separated and the perfection of religious prescribes is unconceivable unless and until we unionize a system of education and politics according to the standard determined by the religion. Present theme of Maududi has tracked to a large number of people to consider that it is our religious obligation to make energetic attempt for an Islamic country similar to other religious duties, as example, offering prayers and keeping fast. Though neither his political party nor Maududi himself has been engaged consistently in political vehemence for political ends, it is hard to give evidence that his educational philosophy and visionary theorization has not sabotaged the constitution of a sound system of politics by twisting together its maturation with religion. It is a reality that the Maudodi’s philosophy still has a widely circulated following in the world. Syed Abul Aa’la Maudodi was a great educationist and philosopher of Islam and a prominent religious of the Islamic world. He presented logics in a philosophical manner and testified that Islam is a perfect and complete code of life. In his Quranic Explanation entitled ‘Tafhim’ul Quran’ acquaints the four reciprocally connected philosophies. He believed essential to understand Quran: Allah Almighty (الہ), Lord (رب), worship (عبادت) and religionمذ ہب)). Profound philosophical cerebrations rooted in Islam that ultimate actuality of Universe is Allah Almighty; furthest source of knowledge is revelation (وحی); every person is an earthly representative of Allah Almighty and he is accountable for his obligations in front of Allah Almighty. As the present study aimed to cater merely few glance of Maudodi’s educational and political ideas in a comprehensive way and developed study on the interpretation of educational ideas in the circumstance of Maudodi’s philosophy. Key Words: Qur’an, Comprehending, Philosophy, Revelation, Religion, Worship, Political Theory.